2016
DOI: 10.1136/bmj.i4645
|View full text |Cite
|
Sign up to set email alerts
|

Association between electronic cigarette use and changes in quit attempts, success of quit attempts, use of smoking cessation pharmacotherapy, and use of stop smoking services in England: time series analysis of population trends

Abstract: ObjeCtivesTo estimate how far changes in the prevalence of electronic cigarette (e-cigarette) use in England have been associated with changes in quit success, quit attempts, and use of licensed medication and behavioural support in quit attempts. DesignTime series analysis of population trends. PartiCiPantsParticipants came from the Smoking Toolkit Study, which involves repeated, cross sectional household surveys of individuals aged 16 years and older in England. Data were aggregated on about 1200 smokers qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
194
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(211 citation statements)
references
References 40 publications
12
194
0
5
Order By: Relevance
“…E-cigarettes are popular cessation aids, and this may have led to increases in the success of quit attempts in the population and quitting as a whole in England and the United States 67…”
Section: Yes—paul Aveyard Deborah Arnottmentioning
confidence: 99%
“…E-cigarettes are popular cessation aids, and this may have led to increases in the success of quit attempts in the population and quitting as a whole in England and the United States 67…”
Section: Yes—paul Aveyard Deborah Arnottmentioning
confidence: 99%
“…Generally, e-cigarettes are used by smokers who want to quit or reduce the smoking of tobacco products [17,22,23,24]. It has been shown that the increased use of e-cigarettes is not associated with an increase in quit attempts, but with an increase in successful quit attempts [25]. …”
Section: Introductionmentioning
confidence: 99%
“…Recent data suggest that vaping does increase the success of quit rates 46. E-cigarettes are generally thought to be a safer alternative to smoking traditional cigarettes, but little is known about the long-term effects of vaping on lung health.…”
Section: Smokingmentioning
confidence: 99%